Exposure and nephrotoxicity concern of bismuth with the occurrence of autophagy. (March 2018) - Liu, Yongming; Shen, Chen; Zhang, Xihui; Yu, Huan; Wang, Fujun; Wang, Yangyun; Zhang, Leshuai W
Metal nanoparticles or metal-based compounds have drawn attention in various fields ranging from industry to medicine because of their unique physicochemical properties. Bismuth (Bi) compounds and nanomaterials have been commonly used in alloys, electronic industry, batteries, and as flame retardants as well as for anti- Helicobacter pylori therapy, while the nanomaterial form has great potential for computed tomography imaging and thermotherapy, both of which will be introduced in this review. Although Bi was used for several decades, there is a lack of detailed information concerning their toxicity and mechanisms on human health. We described the toxicity of Bi on the kidney that seemed to be relatively known by researchers, while the mechanisms remain unclear. Recently, our group has found that Bi compounds, including bismuth nitrate (BN) and Bi nanomaterials, can induce autophagy in kidney cells. We also extended our findings by selecting five Bi compounds, and the results showed that BN, bismuth oxychloride, bismuth citrate, colloidal bismuth subcitrate, and Bi nanomaterials all induced slight cytotoxicity accompanied with autophagy. Although the role of autophagy in Bi-induced cytotoxicity and kidney injury is under investigation by us, autophagy may help with the exploration of the mechanisms of nephrotoxicity by Bi.